ANALISIS KELAYAKAN EKOSISTEM MANGROVE SEBAGAI OBJEK EKOWISATA DI DESA TELUK PAMBANG KECAMATAN BANTAN KABUPATEN BENGKALIS - Ilen Purnama Sari; Defri Yoza; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The mangrove forest is one of the unique and distinctive tropical forest ecosystems because it is a meeting between land and ocean ecosystems. Area of mangrove ecosystems in Bengkalis districtis in Teluk Pambang Village. Reduced width of mangrove forest located in Teluk Pambang Village, Bantan Subdistrict, Bengkalis districtis caused by changes in land use and land functions through a variety of activities of mangrove land conversion. Steps to anticipate the decline in value of mangrove forest ecosystems is by developing ecotourism activities. This study aims to determine the feasibility of the mangrove ecosystem in the Teluk Pambang village, as the object of ecotourism and determine public perceptions of the mangrove ecotourism in Teluk Pambang Village. The method used in analyzing the feasibility of the mangrove ecosystem as an object of ecotourism is based on the analysis of suitability for Yulianda (2007) tour mangrove ecosystems with the results obtained in the natural potential of the field then tabulated. Then, to determine the index of feasibility can be use dequation: IKW =  [Ni/Nmaks] x 100%, for the public perception of ecotourism analyzed descriptively qualitative. The results of this study indicated that the mangrove forest ecosystems in the Teluk Pambang Village included in the category of very decent (SI) for the mangrove ecotourism development. At Station I a value of IKW was 81.57%, Station II the value IKW 94.73%, while the Station III the value IKW 90.78%. The public perception of the ecotourism of mangrove forest in Teluk Pambang village was quite good, so it becomes a the main attraction to be developed as ecotourism and the community a greed that this location is used as a ecotourism of mangrove. Keywords: Feasibility, Mangrove Ecosystems, Ecotourism.